2018
DOI: 10.1542/peds.2017-4169
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal BMI Growth Curves for Surviving Preterm NICU Infants Based on a Large US Sample

Abstract: These new longitudinal curves provide clinicians data on how premature infants' body proportionality changes over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Differences in the child, family and maternal health characteristics by sex and gestational age categories were analysed using independent t-tests, one-way analysis of variance (ANOVA) and chi-squared tests. Based on the previous literature [34][35][36][37][38] and our exploratory analysis, the summarized directed acyclic graph (DAG) between gestational age, daily sleep hours and CSHQ scores (Additional file 1: Figure S1) was generated by using a web-based tool DAGitty (www. dagit ty.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the child, family and maternal health characteristics by sex and gestational age categories were analysed using independent t-tests, one-way analysis of variance (ANOVA) and chi-squared tests. Based on the previous literature [34][35][36][37][38] and our exploratory analysis, the summarized directed acyclic graph (DAG) between gestational age, daily sleep hours and CSHQ scores (Additional file 1: Figure S1) was generated by using a web-based tool DAGitty (www. dagit ty.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional classification based on birth weight centiles for GA does not reflect body fat in both term and preterm newborns 29 , while weight/length greatly aids in predicting newborn fat mass and fat-free mass as well as body proportionality 15 , 30 . BMI is useful for measuring body proportionality for newborn infants 30 32 . PI is a customary measure to evaluate whether abnormalities in growth in preterm infants are symmetric or asymmetric 33 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these outcomes is becomingly increasingly urgent. 11 Studies among children born preterm have found different body shapes compared with children born at term, 12,13 and differences in growth trajectories may be associated with various areas of cognitive function. 14,15 However, the sample size of previous studies was small, [16][17][18] with the largest a uniform sample size of 1320 infants.…”
Section: Introductionmentioning
confidence: 99%